Dialogismo no percurso composicional de György Ligeti - Thayane de Oliveira Ferreira (2012)
The main objective of this study is to investigate the dialogism constitutive of the compositional work of György Ligeti. Treating the musical work as being, similar to the utterance, constitutively dialogic, we had as theoretical support research the bakhtinian dialogism. To achieve the objective of this research, we chose as corpus a work that operates a synthesis of Ligetis compositional language: the Chamber Concerto for thirteen instrumentalists. After the examination of the dialogical relations related to the composer´s work as a whole, we proceed to analysis of the first movement. Throughout the work, we demonstrate that even a purely instrumental work can be analyzed from the perspective of dialogism, in the discursive-musical sense.